2016
DOI: 10.4143/crt.2015.444
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcome of Combined GnRH Agonist and Tamoxifen Is Comparable to That of Sequential Adriamycin and Cyclophosphamide Chemotherapy Plus Tamoxifen in Premenopausal Patients with Lymph-Node–Negative, Hormone-Responsive, HER2-Negative, T1-T2 Breast Cancer

Abstract: PurposeThe purpose of this study was to compare treatment outcomes between combined gonadotropin-releasing hormone agonist and tamoxifen (GnRHa+T) and sequential adriamycin and cyclophosphamide chemotherapy and tamoxifen (AC->T) in premenopausal patients with hormone-responsive, lymph-node–negative breast cancer.Materials and MethodsIn total, 994 premenopausal women with T1-T2, lymph-node–negative, hormone-receptor-positive, HER2-negative breast cancer between January 2003 and December 2008 were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…To the best of our knowledge, at present, there is no randomised controlled trial that compared combined ovarian function suppression and TAM with sequential AC-TAM. The present retrospective study found comparable survival outcome between these two treatment regimens similar to other previous retrospective studies of a Korean population (39,40). There was only one local recurrence in the GnRH-TAM group while in the AC-TAM group, 2 patients with distant metastasis were identified.…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, at present, there is no randomised controlled trial that compared combined ovarian function suppression and TAM with sequential AC-TAM. The present retrospective study found comparable survival outcome between these two treatment regimens similar to other previous retrospective studies of a Korean population (39,40). There was only one local recurrence in the GnRH-TAM group while in the AC-TAM group, 2 patients with distant metastasis were identified.…”
Section: Discussionsupporting
confidence: 88%
“…In breast cancer, mainstream chemotherapy has been changed from CMF to adriamycin/cyclophosphamide (AC), and the difference between OFS therapy and AC has been studied ( 12 , 13 , 25 ). Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…( 13 ) analyzed two groups of patients, an OFS+tamoxifen (n = 260) and a sequential AC+tamoxifen (n = 260) group, among 994 patients with T1-2N0, HR+ HER2- breast cancer with propensity score matching and inverse probability weighting. A comparison of the prognosis over a median follow-up period of 7.4 years showed no difference between the two groups ( 13 ). Sa-Nguanraksa et al.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, inhibition of estradiol (E2) production is the basis of treatment in premenopausal women, and various methods of suppressing the ovarian function, such as ovarian ablation, have been implemented [ 5 ]. In several clinical studies, luteinizing hormone-releasing hormone analogs (LHRHa) are used as an adjuvant therapy after surgery in patients with HR(+), human epidermal growth factor receptor 2 negative (−), and lymph node (+/−) breast cancer, and they are considered a replacement for chemotherapy (CTx) by exerting the same effect as CTx, but with fewer side effects [ 7 8 9 10 11 ]. In clinical studies involving patients with breast cancer, LHRHa is mainly administered as a 1-month regimen (3.75 mg leuprolide, 3.6 mg goserelin, and 3.75 mg triptorelin); therefore, a 1-month formulation is recommended in the guidelines [ 2 3 4 ].…”
mentioning
confidence: 99%
“…Kim et al [ 9 ] reported that LHRHa + T treatment could be an option for premenopausal women with endocrine-responsive, node-negative breast cancer. Sohn et al [ 10 ] showed no difference in recurrence-free, cancer-specific, and overall survival rate after a median follow-up of 5 years. As a result, hormone therapy + LHRHa can replace CTx in certain patients with low tumor burden, such as node-negative tumors, despite the insufficiency of evidence.…”
mentioning
confidence: 99%